TRADITIONS OF N. V. GOGOL AND M. E. SALTYKOV-SHCHEDRIN IN THE SATIRICAL WORKS OF N. N. NOSOV - Rustamova Mokhirakhon (International Journal of Literature and Language Studies, 2026)
The article examines the continuity of the satirical traditions of N. V. Gogol and M. E. Saltykov-Shchedrin in the short prose of N. N. Nosov. The techniques of grotesque, hyperbole, and social contrast adapted by Nosov for a children's audience are analyzed. It is revealed that the writer preserves the critical orientation of classical satire, softening it with a moral attitude and humanistic pathos.